Link between dissolved organic matter transformation and process performance in a membrane bioreactor for urinary nitrogen stabilization. Issue 6 (26th April 2018) - Jacquin, Céline; Monnot, Mathias; Hamza, Razina; Kouadio, Yahaut; Zaviska, François; Merle, Tony; Lesage, Geoffroy; Héran, Marc
Abstract : MBR instabilities during urinary nitrogen stabilization could be identified and explained using 3DEEM. Abstract : A lab-scale membrane bioreactor was fed with fresh urine collected from source separation public toilets to perform full nitrification, urinary nitrogen stabilization and effluent sanitation. After acclimation, a nitrogen loading rate (NLR) of 1.2 kg TN per m 3 d −1 was reached with an average nitrification rate of 98.3%. Dissolved organic matter (DOM) transformation was studied within the MBR to identify biomass activity indicators that could be used for process optimization. By combining three-dimensional excitation emission fluorescence (3DEEM) and liquid chromatography coupled with organic carbon detection, nitrogen detection and UV detection (LC-OCD-OND-UVD), it was possible to investigate the transformation and fate of urine DOM during biological reactions and membrane separation. Results show that urine is mainly composed of low molecular weight molecules (<1000 Da) easily consumed by the active biomass. This consumption came with the production of soluble microbial products (SMP): biopolymers and humic substances. Significant correlations were observed between 3DEEM indicators and the NLR values. Biopolymers were mainly retained by the membrane and tended to accumulate in the reactor, which was of major interest since they were identified as DOM consumed by the active biomass in case of system instabilities. Humic substances were slightly retained by the membrane and mostly implied in irreversible fouling. This original approach allowed highlighting the quick active biomass acclimation under challenging conditions of high strength ammonia solutions such as urine.